Factors Associated With Workplace Bullying and the Mental Health of Construction Industry Apprentices: A Mixed Methods Study - Ross, Victoria; Mathieu, Sharna L.; Wardhani, Rachmania; Gullestrup, Jorgen; Kõlves, Kairi (Frontiers in Psychiatry, 2021)
Young Australian males working in the construction industry are twice as likely to take their own lives than are other young Australian males. This group is also at high risk for poor mental health and alcohol and other drug related harm. Previous research has indicated a bullying culture within this industry, directed particularly towards apprentices and those new to the industry. This Australian study applied an exploratory sequential mixed methods design to explore issues faced by apprentices, estimate the prevalence of bullying and explore the factors associated with bullying and the mental health of apprentices. The results revealed that a significant proportion of construction industry apprentices experience workplace bullying, are exposed to suicidal behaviors, and personally experience suicidal ideation. Multivariate analyses showed that bullying in apprentices was significantly associated with greater psychological distress, as well as being a 3rd year apprentice or not currently in an active apprenticeship. Results also indicated that bullying may be associated with substance use, lower levels of well-being, working nights away from home, the plumbing trades, and working for larger organizations. The outcomes from this study have important implications for the construction industry and will be vital for informing policies and evidence-based interventions to address bullying and mental health in this sector.